Incidence trends, histological subtypes, and topographical distribution of bladder cancer in Iran: a study based on the Iranian National Cancer Registry during 2006-2015 - Naserghandi, Alvand; Azizmohammad Looha, Mehdi; Jameie, Melika; Moradian Haft Cheshmeh, Zeynab; Namakin, Kosar; Golmakani, Najmeh; Feyzi, Aydin; Shabanipour, Hadis; Tofighi Zavareh, Mohammad Amin; Allameh, Farzad; Akbari, Mohammad Esmaeil (Frontiers in Oncology, 2024)
BackgroundBladder cancer (BCa) is a significant public health concern. This study aimed to analyze the incidence trends, histological subtypes, and topographical distribution of BCa in Iran over a decade.MethodsThis retrospective registry-based study analyzed data on BCa patients diagnosed between March 20, 2006, and March 20, 2015. Following data quality control, age-standardized incidence rates (ASIRs) were calculated for BCa overall, by sex and histological subtype using the new World Health Organization (WHO) standard population.ResultsWe identified 51,379 BCa cases (81.97% male) with a mean age of 65.10 ± 14.89 years. The overall ASIR was 8.92 per 100,000 (95% CI: 8.84-9.00). While a modest increase in ASIR was observed overall (8.77 in 2006 to 9.64 in 2015) and among males (14.13 in 2006 to 15.95 in 2015) during the study period, males consistently had a significantly higher ASIR compared to females (approximately 4.5:1 ratio). BCa incidence showed a progressive increase across older age groups, particularly those aged 40-44 to 80-84 years. Urothelial cell carcinoma (UCC) was the most prevalent histological type (ASIR: 8.19 to 7.93), followed by adenocarcinoma (AC; ASIR: 0.13 to 0.11). Squamous cell carcinoma (SCC) displayed a decreasing trend (ASIR: 0.11 to 0.06). Both UCC and AC were more frequent in males (approximately 5 and 3 times higher than females, respectively). Malignant neoplasm of the bladder, unspecified, constituted over 95% of BCa topography classifications.ConclusionThis study identified a modest rise in BCa incidence, with male predominance and a higher burden in older adults. Further investigation into potential risk factors contributing to this increase is warranted.